Manganese-Enhanced Magnetic Resonance Imaging: Overview and Central Nervous System Applications With a Focus on Neurodegeneration - Cloyd, Ryan A.; Koren, Shon A.; Abisambra, Jose F. (Frontiers in Aging Neuroscience, 2018)
Manganese-enhanced MRI (MEMRI) rose to prominence in the 1990s as a sensitive approach to high contrast imaging. Following the discovery of manganese entry through calcium-permeable channels, MEMRI applications expanded to include functional imaging in the CNS and other body systems. MEMRI has since been employed in many animal models and in humans to better understand physiology and disease. This article will review the evolution of applied MRI research into MEMRI. Furthermore, we discuss current in vivo MEMRI applications in the brain and the clinical use of the chelated manganese compound mangafodipir in humans.